Functional MRI Characteristics in Visual Cortex (BA 17, 18 and 19) Corresponding to the Visual Field of Normal, Glaucoma Suspect (GS) and Primary Open Angle Glaucoma (POAG) Patients - Nurul Hanim, Nasaruddin; Ahmad Nazlim, Yusoff; Sharanjeet, Kaur (Fakulti Sains Kesihatan (Faculty of Health Sciences) and Penerbit UKM (UKM Press), 2017)
The purpose of this study was to characterize, differentiate and correlate visual field and brain activation in visual cortex for normal, glaucoma suspect (GS) and primary open angle glaucoma (POAG) participants using Standard Automated Perimetry (SAP) and functional Magnetic Resonance Imaging (fMRI) respectively. The fMRI scans and SAP test were both carried out in Pusat Perubatan Universiti Kebangsaan Malaysia (PPUKM). Two types of black-and-white checkerboard pattern were displayed to the participants during the fMRI scans. The fMRI data were analyzed using WFU pickatlas toolbox targeting visual cortex area. The results showed that there was no significant difference in number of activated voxel between the three groups in visual cortex (BA 17, 18 and 19) while viewing all the given stimuli (p > 0.05). The pattern standard deviation (PSD) of SAP for visual field also revealed no significant differences (p > 0.05) in all groups of participants. However, negative correlation between PSD and fMRI activation was observed. The PSD values increased with a decrease in fMRI activation. With reference to visual field analysis, the results suggest that glaucomatous neuropathy of POAG patients has led to a gradual decrease in visual cortex activation and a gradual increase in PSD